Experimental study on fatigue performance of UHPC-orthotropic steel composite deck. (September 2019) - Chen, Shiming; Huang, Yang; Gu, Ping; Wang, Jun-Yan
Abstract: UHPC-orthotropic steel composite deck is an innovative and efficient bridge deck system, however the failure mode of this composite bridge deck under fatigue load is still not well understood, particularly when the deck is in hogging bending. To investigate the fatigue behavior of the UHPC-orthotropic steel composite deck, two multi-span full scale composite bridge decks in hogging bending were experimentally studied. To simulate the bridge deck under negative bending, the specimens were designed with the mid-span deck simply supported and two overhanging decks each side. Each specimen was tested twice. In the first test phase, the specimen was loaded with a vertical force acting on one side span, while in the second test phase, the specimen was vertically loaded on another side span. Tests revealed that among the all fatigue-prone details of an orthotropic steel deck, only the longitudinal cracks were observed occurring in the low portion of rib web which was near the weld toe of the rib to the transverse diaphragm. The fatigue strength of these specific cracks longitudinally orientated can be evaluated in a term of the vertical stress range of the rib below the weld toe under the fatigue details category C of AASHTO or category 71 MPa of Eurocode3. Shear connection failure of the composite deck was also found featuring with delamination between UHPC and steel bridge deck. Fatigue damage of the short headed studs was further inspected and evaluated by means of drilling test. It is found that the fatigue life of the shear connection is governed by the fatigue shear strength of the short headed studs, which is much longer than the fatigue life codified in the specifications for studs of conventional composite beams. The fatigue shear connection strength of the composite bridge deck can be assessed conservatively in a term of the fatigue shear strength of the headed studs. Highlights: Fatigue behavior of composite bridge deck under negative bending was experimentally investigated. Two typical fatigue failures were found. Inelastic range of UHPC did not influence the overall performance Longitudinal cracks can be evaluated by the vertical stress range below the weld toe. The fatigue shear connection strength can be assessed conservatively by the fatigue shear strength of the headed studs.